Mitigating Latent Threats Identified through an Embedded In Situ Simulation Program and Their Comparison to Patient Safety Incidents: A Retrospective Review - Knight, Philip; MacGloin, Helen; Lane, Mary; Lofton, Lydia; Desai, Ajay; Haxby, Elizabeth; Macrae, Duncan; Korb, Cecilia; Mortimer, Penny; Burmester, Margarita (Frontiers in Pediatrics, 2018)
ABSTRACT: Objective To assess the impact of service improvements implemented because of latent threats (LT) detected during in-situ simulation. Design Retrospective review from April 2008 to April 2015. Setting Paediatric Intensive Care Unit (PICU) in a specialist tertiary hospital. Intervention Service improvements from LTs detection during in-situ simulation. Action plans from patient safety incidents (PSIs). Main Outcome Measures The quantity, category and subsequent service improvements for LTs. The quantity, category and subsequent action plans for PSIs. Similarities between PSIs and LTs before and after service improvements. Results 201 Simulated inter-professional team training courses with 1144 inter-professional participants. 44 LTs were identified (1 LT per 4.6 courses). Incident severity varied: 18 (41%) with the potential to cause harm, 20 (46%) that would have caused minimal harm and 6 (13%) that would have caused significant temporary harm. Category analysis revealed the majority of LTs were resources (36%) and education and training (27%). The remainder consisted of equipment (11%), organisational and strategic (7%), work and environment (7%), medication (7%), and systems and protocols (5%). 43 service improvements were developed: 24 (55%) resources/equipment; 9 (21%) educational; 6 (14%) organisational changes; 2 (5%) staff communications; and 2 (5%) guidelines. 4(9%) service improvements were adopted trust-wide. 32(73%) LTs did not recur after service improvements. 24 (1%) of 1946 PSIs were similar to LTs: 7 resource incidents, 7 catastrophic blood loss (CBL), 4 hyperkalaemia arrests, 3 emergency buzzer failures, 3 difficulties contacting staff. 34 LTs (77%) were never recorded as PSIs. Conclusion An in-situ simulation programme can identify important LTs which traditional reporting systems miss. Subsequent improvements in workplace systems and resources can improve efficiency and remove error traps. Key words: Patient Safety Incident reporting and Analysis Quality improvement Education Simulation In-situ characterization